Another autopsy on Britain’s balance of payments: 1958-1967 - THIRLWALL, A.P. (PSL Quarterly Review, 2014)
The article deals with Britain’s balance of payments on international account from 1958 to 1967. In particular, the author looks at whether or not devaluation was appropriate in 1964, and whether or not the Labour Government was wise in rejecting devaluation as a solution to the payments deficit, while resorting to it in 1967. A thorough analysis of the origins of payments disequilibrium in these two years is provided, as well as a comparison of these years with previous years. It is suggested that the “underlying” balance of payments on trade and current account remained virtually unchanged over the period 1960-1967, that the slightly greater deficit on current account in 1964 than in 1960 can largely be accounted for by the rate at which demand expanded in 1964, and that in general Britain’s payments troubles have had little to do with growing price uncompetitiveness in world markets. JEL: F32, E41